2017
DOI: 10.3389/fpubh.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Student-Led, Community-Based, Multifactorial Fall Prevention Program: Stay in Balance

Abstract: BackgroundFalls are a major public health concern in older adults. Recent fall prevention guidelines recommend the use of multifactorial fall prevention programs (FPPs) that include exercise for community-dwelling older adults; however, the availability of sustainable, community-based FPPs is limited.MethodsWe conducted a 24-week quasi-experimental study to evaluate the efficacy of a community-based, multifactorial FPP [Stay in Balance (SIB)] on dynamic and functional balance and muscular strength. The SIB pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Results suggest that although risk for falls and fall mortality are closely linked, individuals who are more likely to fall are not necessarily more likely to die from fall-related injuries. Fall-related mortality prevention efforts should focus on combined strategies to reduce fall hazards (26)(27)(28)(29)(30) and to identify individuals who may be less resilient to falls (31)(32)(33). Further consideration of the methodological challenges of reporting and estimating fall-related mortality incidence is also warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggest that although risk for falls and fall mortality are closely linked, individuals who are more likely to fall are not necessarily more likely to die from fall-related injuries. Fall-related mortality prevention efforts should focus on combined strategies to reduce fall hazards (26)(27)(28)(29)(30) and to identify individuals who may be less resilient to falls (31)(32)(33). Further consideration of the methodological challenges of reporting and estimating fall-related mortality incidence is also warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the American Geriatrics Society emphasized the assessment of fall risk factors, multi-faceted interventions, and environment adjustments to prevent falls [ 67 ]. It was observed that multi-faceted programs consisting of exercise therapy and education on exercise, nutrition, and environmental adjustment were effective in preventing falls [ 68 ]. A systematic literature review study also suggested the necessity of studies on complex programs that consider physical factors such as balance improvement and psychological factors including depression and cognitive levels [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their vibrancy, acquired professional knowledge and skills, as well as their awareness of local cultural customs, medical students have been well-accepted as a force multiplier for the community-based health service [17][18][19][20]. For example, medical students were involved in a student-led community-based prevention program for falls, which has been demonstrated to potentially enhance the sustainability of the program and reduce program costs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their vibrancy, acquired professional knowledge and skills, as well as their awareness of local cultural customs, medical students have been well-accepted as a force multiplier for the community-based health service [17][18][19][20]. For example, medical students were involved in a student-led community-based prevention program for falls, which has been demonstrated to potentially enhance the sustainability of the program and reduce program costs [17]. Our team previously recruited undergraduate students from medical and other health professions to participate in household visits for community residents suffering from diabetes aiming to increase diabetes self-management education [18].…”
Section: Introductionmentioning
confidence: 99%